Granulated material, steelmaking method, and method for producing granulated material

The production of granulated products with specific particle size and strength using uncompressed molding with Portland cement addresses the inefficiencies of recycling fine powders, enhancing recycling efficiency and production yield for refining furnace applications.

JP7628842B2Active Publication Date: 2025-02-12NIPPON STEEL CORPORATION +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021037661
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-09
Publication Date
2025-02-12
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

Recycling fine powders of waste refractory, slag, and dust is inefficient due to increased gas ejection and low production efficiency, especially when used as auxiliary raw materials in refining furnaces, and existing briquette molding methods are not optimal for high-yield production.

Method used

Production of granulated products with a particle size distribution of 5mm to 50mm and a crushing strength of 35kgf to 70kgf using uncompressed molding with Portland cement as a binder, involving steps of adding binder and water, forming the kneaded product, and sieving to achieve optimal particle size distribution.

Benefits of technology

The method enhances recycling efficiency by forming granulated products with desired properties, allowing them to be used as auxiliary materials in refining furnaces with improved handling and yield, reducing gas ejection and increasing production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628842000004
    Figure 0007628842000004
  • Figure 0007628842000005
    Figure 0007628842000005
  • Figure 0007628842000006
    Figure 0007628842000006
Patent Text Reader

Abstract

To recycle powdered raw material with high production efficiency.SOLUTION: Granules are formed from a raw material containing at least one of refractory waste, slag or dust, have a grain size distribution of 5 mm or more and less than 50 mm, and a collapse strength of 35 kgf or more and 70 kgf or less. A method for producing granules includes the steps of: adding a binder and water to a raw material containing at least one of refractory waste, slag or dust, making a mixture; subjecting the mixture to non-compression molding, making granules; and sieving the granules to have a grain size distribution of 5 mm or more and less than 50 mm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a granulated material. , Steelmaking method and a method for producing a granulated product. [Background technology]

[0002] In recent years, the demand for recycling these waste materials has been increasing due to the decrease in the number of disposal destinations for waste refractories containing slag and dust, the increase in disposal costs, and the increase in the price of auxiliary materials for steelmaking. Known destinations for recycling include, for example, refractory repair materials, and auxiliary materials for refining furnaces such as slag-making materials or slag foaming suppressants. As a technology related to such recycling, Patent Document 1 describes a technology in which refractory blocks are crushed, sieved as necessary, and adjusted to a predetermined particle size range, and then used as is as an agent for suppressing slag foaming generated in the steelmaking refining process. Patent Document 2 also describes a technology in which waste refractories mainly composed of MgO are crushed to 5 mm or less, and a binder and water are added and kneaded to form into a briquette shape to produce a slag concentration adjuster. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-2915 A [Patent Document 2] Japanese Patent Application Publication No. 10-317040 Summary of the Invention [Problem to be solved by the invention]

[0004] However, when raw materials such as waste refractories, slag, and dust are in a fine powder form, it is difficult to recycle them as refractory repair materials. In addition, as described in Patent Document 1, when waste refractories are used as auxiliary materials to be charged into a refining furnace, waste refractories with a relatively large particle size are used. If waste refractories, slag, and dust are charged in a fine powder form, they are lifted up by the gas flow generated in the furnace and discharged together with the exhaust gas at a high rate, so that sufficient effects cannot be obtained. As described in Patent Document 2, if the fine powder raw materials are formed into briquettes, they can be used as auxiliary materials to be charged into a refining furnace, but the formation of briquettes requires a process of putting the kneaded raw materials into a mold and compressing them, so the production efficiency is not necessarily high.

[0005] Therefore, the present invention provides a granulated material that enables recycling of fine powder raw materials with high production efficiency. , Steelmaking method Another object of the present invention is to provide a method for producing a granulated product. [Means for solving the problem]

[0006] [1] Granulated material formed from raw materials containing at least one of waste refractory material, slag, or dust, having a particle size distribution of 5 mm or more and less than 50 mm, and a crushing strength of 35 kgf or more and 70 kgf or less. [2] The granulated material according to [1], in which Portland cement is added as a binder. [3] A slag foaming sedative containing 50% by mass or more of the granulated material described in [1] or [2]. [4] A slag-forming material containing 50% by mass or more of the granulated material described in [1] or [2]. [5] A method for producing a granulated material, comprising: a step of adding a binder and water to a raw material containing at least one of waste refractory material, slag, and dust to produce a kneaded material; a step of non-compressively molding the kneaded material to produce a granulated material; and a step of sieving the granulated material so that the particle size distribution is 5 mm or more and less than 50 mm. [6] The method for producing a granulated material according to [5], further comprising adding water to the raw material so that the sum of the raw material moisture content and the added moisture content is 13% by mass or more and 16% by mass or less. [7] The method for producing a granulated material according to [5] or [6], wherein the binder is Portland cement. [8] The method for producing a granulated material according to any one of [5] to [7], wherein the step of producing a kneaded material includes an empty kneading step for 1 minute or more. [9] A method for producing a granulated material described in any one of [5] to [8], wherein the step of generating a granulated material includes a step of reversing the rotation direction of the arms of the granulator.

[10] A method for producing a granulated material described in any one of [5] to [9], further comprising a drying step for two days or more. Effect of the Invention

[0007] According to the above-mentioned configuration, even if the raw material contains at least one of waste refractory, slag, and dust, the raw material is in a fine powder form, it can be processed into granules having a predetermined particle size and strength, and can be recycled as, for example, an auxiliary raw material to be charged into a refining furnace. Since the granules are formed by non-compression molding, the production efficiency can be improved compared to the case where the granules are formed by compression molding. [Brief description of the drawings]

[0008] [Figure 1] 1 is a photograph for explaining the optimal particle size distribution of pellets. [Diagram 2] 1 is a graph showing the strength of pellets in each study example. [Diagram 3] 1 is a graph showing the particle size distribution of pellets in each study example. [Figure 4] 1 is a graph showing the relationship between the drying period and strength of pellets after granulation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A preferred embodiment of the present invention will be described in detail below with reference to the accompanying drawings. In this specification and the drawings, components having substantially the same functional configurations are designated by the same reference numerals to avoid repetitive explanation. Furthermore, % indicating a percentage means % by mass unless otherwise specified.

[0010] In an embodiment of the present invention, a granulated material is produced from a fine powder raw material containing at least one of waste refractory, slag, and dust. The raw material used in this embodiment is, for example, a mixture of used alumina-based refractory and slag, or a mixture of used dolomite brick chips and stainless steel dust, but is not limited to these examples. Fine powder means that the particle size is less than 5 mm, but all of the raw material does not have to be fine powder, and raw materials that are not fine powder, i.e., have a particle size of 5 mm or more, may be used together with the fine powder raw material.

[0011] In this embodiment, in order to improve the particle size distribution of the raw material including at least one of the waste refractory, slag, and dust, and to enable the raw material to be fed into a refining furnace and to improve production efficiency, the raw material is molded into pellets using cement and water as binders. Here, both the briquettes and the pellets are granulated products, but the briquettes are different in that the briquettes are granulated products that have been compressed and the pellets are granulated products that have been non-compressed. That is, the process of molding the raw material into pellets in this embodiment does not include a compression process. As a result, in this embodiment, it is possible to improve production efficiency compared to, for example, a case in which the raw material is compressed and molded into a briquette. The fact that the manufactured granulated product is a non-compressed pellet can be identified by the difference in strength from the compressed briquettes, as described later.

[0012] FIG. 1 is a photograph for explaining the optimum particle size distribution of pellets used as auxiliary raw materials to be charged into a refining furnace. The inventors conducted an experiment to identify the optimum particle size distribution when forming raw materials into pellets and using them as auxiliary raw materials to be charged into a refining furnace. In the experiment, a mixture of used refractories and slag formed into pellets was used, which was sieved into three particle size distributions. In the example shown in FIG. 1(a), the particle size d is less than 5 mm, in the example shown in FIG. 1(b), the particle size d is 5 mm or more and less than 25 mm, and in the example shown in FIG. 1(c), the particle size d is 30 mm or more and less than 50 mm. The results of using about 30 charges of each of the three types of pellets in a converter as a slag foaming quencher are shown in Table 1.

[0013] [Table 1]

[0014] In a converter, if the slag foaming is not sufficiently stabilized, the tapping is not completed in one tap and another tapping is required, so the slag sedation effect of the sedation agent can be evaluated by the average number of tapping times per charge. In the results shown in Table 1, when the grain size d is less than 5 mm, the average number of tapping times is 1.8, and most charges require two or more tapping times. In contrast, when the grain size d is 5 mm or more and less than 25 mm, and when the grain size d is 30 mm or more and less than 50 mm, the average number of tapping times is 1.1, and most charges complete tapping in one tap. From this result, it can be seen that when the grain size d is less than 5 mm, most of the pellets introduced as a slag foaming sedation agent are lifted up by the gas flow and do not reach the molten metal surface, and the slag sedation effect is insufficient. Therefore, in this embodiment, the pellet manufacturing conditions are optimized so that granulated products with a grain size distribution of 5 mm or more and less than 50 mm are obtained.

[0015] In this embodiment, the method for producing pellets as the granulated product includes a step of adding a binder and water to the raw material to produce a kneaded product, a step of non-compressively molding the kneaded product to produce pellets, and a step of sieving the pellets so that the particle size distribution is 5 mm or more and less than 50 mm. In optimizing the production conditions for the pellets, the production conditions in the kneading and granulation steps were considered so that the yield of pellets having a particle size distribution of 5 mm or more and less than 50 mm would be sufficiently high in the sieving step.

[0016] Table 2 shows the manufacturing conditions of the pellets in the study example. In each of No. 1 to No. 9, the raw material used was a mixture of used alumina-based refractory and slag, and the grain size of the raw material was less than 5 mm. A pelletizer (Pellegaia (registered trademark) mixer) equipped with the functions of a kneader and a granulator was used to form the pellets, and the raw material, binder and water were kneaded and granulated as a series of processes. Portland cement was used as the binder, and the binder amount (external amount relative to the raw material) was changed in the range of 5% to 15%. In addition, the amount of water added was set according to the total moisture content, which is the sum of the raw material moisture content and the added moisture content, and the total moisture content was changed in the range of 12% to 17%. Here, the moisture content is calculated for the raw material and water without the binder. The empty kneading in the kneading process, that is, the pre-kneading of the binder and raw material before adding water, is usually performed for 15 seconds, but in No. 6 and No. 9, it was performed for 1 minute. In addition, regarding the rotation of the arms during granulation in the Pellegaia (registered trademark) mixer, normally the arms rotate in one direction at a constant speed, but in No. 7 the arms rotate in one direction while the rotation speed is changed to a low speed in the latter half of the granulation process, and in No. 8 and No. 9 the arms rotate at a constant speed while the rotation direction is reversed in the latter half of the granulation process.

[0017] [Table 2]

[0018] FIG. 2 is a graph showing the strength of the pellets in each of the study examples. In each of the study examples shown in Table 2, the pellets obtained in the granulation process were dried for 2 to 3 days, with a loosening process to prevent adhesion between particles, and then the crushing strength was measured using a crushing strength tester as specified in JIS Z8841. In the results shown in the graph of FIG. 2, when comparing No. 1, No. 2, and No. 3, the strength of No. 2, which has a total moisture content of 14%, is greater than the strengths of No. 1 and No. 3, which have total moisture contents of 12% and 17%, respectively, and it can be seen that the strength of the pellets is improved by setting the total moisture content within an appropriate range. In addition, when comparing No. 2, No. 4, and No. 5, the strength of No. 2, which has a binder amount (outer coating) of 10%, is higher than the strength of No. 4, which has a binder amount of 5%, and the strength of No. 5, which has a binder amount of 15%, is even higher, so it can be seen that the strength of the pellets is improved by increasing the binder amount. Furthermore, comparing No. 2, No. 6, No. 7 and No. 8, the strength of the granules was greatly improved in No. 6, where the idle mixing time was reduced from 15 seconds to 1 minute, and in No. 8, where the rotation direction of the arm was reversed during granulation, whereas the strength of the granules was not improved much in No. 7, where the rotation speed of the arm was changed during granulation, indicating that extending the idle mixing time or reversing the rotation direction during granulation is more effective in improving the strength of the pellets. No. 9 is an example where the manufacturing conditions were optimized based on the above findings, and the average strength was 55 kgf, the highest among all the examples.

[0019] Here, the strength of the pellets is not directly related to the effect itself when the pellets are used as a secondary raw material to be charged into a refining furnace, such as a slag foaming sedative, but it is an important index in terms of preventing the effect from being fully exerted due to cracks occurring during transportation or charging, causing the particle size to decrease from that at the time of production. Specifically, by giving the pellets a crushing strength of 35 kgf or more, the same means of transportation and charging as for normal secondary raw materials can be used, and sufficient handling can be achieved. Among the examined examples, No. 5, No. 6, No. 8, and No. 9 meet this strength standard. In addition, if the strength is high, the particles are less likely to crumble during the sieving process, improving the yield. In the case of pellets that are not compressed and molded with an appropriate binder amount, the crushing strength is an upper limit of 70 kgf. In the case of briquettes that are compressed and molded with the same material, the crushing strength becomes about 90 kgf when dried, so in this respect they can be distinguished from the pellets that are the granulated product according to this embodiment.

[0020] FIG. 3 is a graph showing the particle size distribution of the pellets in each of the examples. In each of the examples shown in Table 2, the granulated material was sieved after drying to measure the particle size distribution. In the results shown in the graph of FIG. 3, the particle size of the granulated material in No. 1 was noticeably small, and the proportion of granulated material in the above-mentioned particle size distribution of 5 mm or more and less than 50 mm was about 20%. In addition, in No. 3, the moisture content was too high, making it difficult to measure the particle size distribution by sieving. In No. 4, the particle size distribution itself could be measured, but the binder amount was small, resulting in a state similar to that of a case with too much moisture, and it was not suitable for practical use. In the other examples, that is, No. 2 and No. 5 to No. 9, the proportion of granulated material in the particle size distribution of 5 mm or more and less than 50 mm was approximately 50% or more, and was suitable for practical use. This means that when the pellets in each study example are used as a slag foaming stabilizing agent or slag former, as described later, 50% or more of the granules in the particle size distribution of 5 mm to 50 mm are contained in the slag foaming stabilizing agent or slag former. The highest yield was No. 9, where the proportion of granules in the particle size distribution of 5 mm to 50 mm reached 75%.

[0021] Figure 4 is a graph showing the relationship between the drying period and strength of pellets after granulation. With the blending of raw materials and binder (Portland cement) shown in Table 3, pellets after granulation were dried both indoors and outdoors, and the crushing strength was measured after a specified number of days had passed. As shown in the graph in Figure 3, in all cases, the strength increases significantly up to two days, but thereafter the change in strength becomes smaller. Therefore, it is considered that a drying period of two days or more is preferable in order to fully develop the strength of the pellets after granulation.

[0022] [Table 3]

[0023] From the results of the above studies, the following are listed as the manufacturing conditions for pellets to obtain granules with a particle size distribution of 5 mm or more and less than 50 mm. Note that, as shown by the above study example, it is not necessary to satisfy all of the manufacturing conditions, and the particle size distribution of the pellets can be optimized by combining any of the following conditions according to the physical properties of the raw materials and the characteristics of the manufacturing equipment.

[0024] Add 10% or more Portland cement as a binder. Portland cement has a longer setting time, i.e., the time it takes for it to develop strength after being mixed with water, compared to other types of cement such as alumina cement, and therefore allows stable granulation without the mixture of raw materials, binder, and water solidifying prematurely, which makes granulation difficult. The amount of Portland cement added is preferably 10% or more in terms of outer percentage, from the viewpoint of ensuring the strength of the granulated product. If too much binder is added, the moldability during granulation decreases, so the upper limit of the amount of Portland cement added may be, for example, about 20% in outer percentage.

[0025] -Adjust the amount of water added so that the total moisture content is between 13% and 16%. If the total moisture content, which is the sum of the raw material moisture content and the added moisture content, is too low, the particle size of the granulated material will be too small, resulting in a decrease in yield. Also, if the total moisture content is too high, the strength of the granulated material will be low, and the moisture content may be too high for practical use. Therefore, it is preferable to adjust the total moisture content to an appropriate range, for example, as described above. Here, the waste refractory, slag, and dust that are the raw materials are originally discharged from a dry environment, but since they absorb moisture due to rainwater during storage, for example, if the amount of moisture added is adjusted only by the added moisture content, the amount of moisture may become too high. Therefore, it is preferable to adjust the amount of moisture added by the total moisture content as in this embodiment.

[0026] In the kneading process, extend the time of the empty kneading process. -In the granulation process, the rotation direction of the granulator arms is reversed. In addition to adjusting the amount of binder and water added, the strength of the granulated material can be increased by promoting the mixing of the raw materials with the binder and water by performing an empty kneading process for one minute or more or by reversing the direction of rotation of the granulator's arms, thereby improving the handling properties and yield. The Pellegaia (registered trademark) mixer is an example of a pelletizer that performs kneading and granulation as a series of processes and can reverse the direction of rotation of the arms in the granulation process, but other kneading machines and granulators can also be used.

[0027] The drying process is carried out for a period of at least 2 days. Since the strength of the granulated material is developed by coagulation of the binder after granulation, it is preferable to carry out the drying step for a period of 2 days or more.

[0028] According to the embodiment of the present invention as described above, raw materials including at least one of waste refractory, slag, and dust can be recycled as, for example, a secondary raw material to be charged into a refining furnace by processing the raw materials into granules having a predetermined grain size and strength even if the raw materials are in a fine powder form. In this embodiment, the granules are pellets formed by non-compression molding, so that production efficiency can be improved compared to the case where the granules are formed by compression molding. The manufactured granules can be used as a slag foaming suppressant as in the above example, and can also be used as a smoke suppressant. These slag foaming suppressants or smoke suppressants are charged into, for example, a slag ladle, a molten iron ladle, or a ladle. The above-mentioned granules may also be used as a secondary raw material to be charged into a refining furnace for other purposes, such as a slag former. The use of the granules is not limited to a secondary raw material to be charged into a refining furnace, and they can also be used for other purposes, such as a repair material for damaged parts of lining bricks of a converter or an electric furnace.

[0029] Although the preferred embodiment of the present invention has been described in detail above with reference to the accompanying drawings, the present invention is not limited to such an example. It is clear that a person having ordinary knowledge in the technical field to which the present invention pertains can conceive of various modified or altered examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally belong to the technical scope of the present invention.

Claims

1. A granulated material formed from fine powder raw materials including waste refractories or slag, having a particle size distribution of 5 mm or more and less than 50 mm, a crushing strength of 35 kgf or more and 70 kgf or less, and containing Portland cement as a binder.

2. A steelmaking method using a smelting furnace-charged auxiliary material containing 50 mass % or more of the granulated material according to claim 1 as a slag foaming quencher.

3. A steelmaking method using a slag forming material as an auxiliary raw material to be charged into a smelting furnace, the auxiliary raw material containing 50 mass % or more of the granulated material according to claim 1 .

4. A step of adding a binder and water to a fine powder raw material containing waste refractory material or slag to generate a kneaded material; A step of non-compressively molding the kneaded product to produce a granulated product; sieving the granulated product so that the particle size distribution is 5 mm or more and less than 50 mm; Including, The method for producing a granulated product, wherein the binder is Portland cement.

5. The method for producing a granulated product according to claim 4, further comprising a drying step for 2 days or more.

Citation Information

Patent Citations

  • Foaming killing agent

    JP1987086110A

  • Production of slag killing material for steelmaking

    JP1997310112A

  • Mgo(Magnesium oxide) briquette for adjusting slag concentration

    JP1998317040A

  • Method for refining molten iron

    JP2002309312A

  • Method of using refractory for slag foaming depressant, and slag foaming depressant

    JP2004002915A